Semi-automatic system of lumen measurement of LED lights in an embedded box - Toyan, Md. Aftahee; Masud, Ahmed Shahriar; Amin, Sams Shafiul; Jeeval, Faiad Raihan Hafiz (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.